Arcuate AgRP, but not POMC neurons, modulate paraventricular CRF synthesis and release in response to fasting - Alves Fernandes, Alan Carlos (2022)
Background: The activation of the hypothalamic–pituitary–adrenal (HPA) axis is essential for metabolic adaptation in response to fasting. However, the neurocircuitry connecting changes in the peripheral energy stores to the activity of hypothalamic paraventricular corticotrophin-releasing factor (CRFPVN) neurons, the master controller of the HPA axis activity, is not completely understood. Our main goal was to determine if hypothalamic arcuate nucleus (ARC) POMC and AgRP neurons can communicate fasting-induced changes in peripheral energy stores, associated to a fall in plasma leptin levels, to CRFPVN neurons to modulate the HPA axis activity in mice. Results: We observed increased plasma corticosterone levels associate with increased CRFPVN mRNA expression and increased CRFPVN neuronal activity in 36 h fasted mice. These responses were associated with a fall in plasma leptin levels and changes in the mRNA expression of Agrp and Pomc in the ARC. Fasting-induced decrease in plasma leptin partially modulated these responses through a change in the activity of ARC neurons. The chemogenetic activation of POMCARC by DREADDs did not affect fasting-induced activation of the HPA axis. DREADDs inhibition of AgRPARC neurons reduced the content of CRFPVN and increased its accumulation in the median eminence but had no effect on corticosterone secretion induced by fasting. Conclusion: Our data indicate that AgRPARC neurons are part of the neurocircuitry involved in the coupling of PVNCRF activity to changes in peripheral energy stores induced by prolonged fasting.